2007
DOI: 10.5326/0430027
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Clinical Trial of Combination Chemotherapy With Dexamethasone for Lymphoma in Dogs

Abstract: Dogs with histologically confirmed lymphoma were treated with a 14-week induction chemotherapy protocol that included dexamethasone. A phase II clinical trial was done using a standard two-stage design. Complete remission occurred in 21 (88%) dogs, with a median initial progression-free interval of 186 days. Toxicity was mild and self-limiting in the majority of dogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
6
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 40 publications
5
6
0
Order By: Relevance
“…The chemotherapy protocol described in our study was associated with a lower ORR (84%; 68% CR) when compared with contemporary previously reported CHOP protocols (ORR 93–100%; 73–96% CR), but the response rate appeared equivalent to that reported after single‐agent DOX treatment (ORR, 74–87%; 52–78% CR) . Interestingly, despite the lower ORR, the 194‐day median PFI reported in our study appears comparable to PFIs after CHOP‐based treatment as reported by others (140–219 days), and superior to outcomes reported after single‐agent DOX (median response durations, 80.5–169 days) . Many earlier studies failed to report PFI, a measure that incorporates both responding and nonresponding dogs, and rather reported response duration, which excludes dogs experiencing SD or PD as their best responses, making comparisons with these studies challenging.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The chemotherapy protocol described in our study was associated with a lower ORR (84%; 68% CR) when compared with contemporary previously reported CHOP protocols (ORR 93–100%; 73–96% CR), but the response rate appeared equivalent to that reported after single‐agent DOX treatment (ORR, 74–87%; 52–78% CR) . Interestingly, despite the lower ORR, the 194‐day median PFI reported in our study appears comparable to PFIs after CHOP‐based treatment as reported by others (140–219 days), and superior to outcomes reported after single‐agent DOX (median response durations, 80.5–169 days) . Many earlier studies failed to report PFI, a measure that incorporates both responding and nonresponding dogs, and rather reported response duration, which excludes dogs experiencing SD or PD as their best responses, making comparisons with these studies challenging.…”
Section: Discussionsupporting
confidence: 65%
“…The current standard of care for the treatment of dogs with multicentric lymphoma is combination chemotherapy including cyclophosphamide, doxorubicin (DOX), vincristine, and prednisone (CHOP) . Objective response rates (ORR) of ≥85%, median response durations of 6–10 months, and median overall survival times of 8–12 months have been reported with CHOP‐based protocols . Most dogs that achieve remission after a CHOP‐based chemotherapy protocol eventually relapse, with <25% of patients experiencing survival times >2 years .…”
mentioning
confidence: 99%
“…In this study, we found no correlation between DTH response and DFI. The median DFI with our combination of chemotherapy and immunotherapy was comparable to that seen in retrospective studies which evaluated short CHOP‐based chemotherapy protocols alone 53–56 . However, comparisons should be made with caution owing to the small sample size and selection bias for dogs in remission in our study as well as differences in the chemotherapy protocols and study populations between the studies.…”
Section: Discussionsupporting
confidence: 66%
“…Among the 33 dogs that received treatment involving doxorubicin, 8 (24%) were treated with a standard combination chemotherapy protocol, 25 22 (67%) were treated with a short induction-only protocol, 26 2 (6%) were treated with doxorubicin and l-asparaginase, and 1 (3%) was treated with doxorubicin and an anti-lymphoma monoclonal antibody. 27 *Bone marrow data were missing from 4 nonanemic dogs, thereby precluding complete staging of the neoplasia.…”
Section: Resultsmentioning
confidence: 99%